The diagnostic value of circulating microRNAs as a biomarker for gastric cancer: A meta-analysis - Wei, Hui (Oncol Rep, 2019)
Recently, cancer research microRNA studies have drawn great attention. However, the results of these studies have been inconsistent and variable regarding the availability of circulating miRNAs in gastric cancer (GC) diagnosis. Thus, results should be interpreted cautiously. The purpose of the present study was to assess the diagnostic performance of circulating miRNAs in GC diagnosis. We conducted a systematic and comprehensive approach for the inclusion of studies. The sensitivity, specificity, and diagnostic odds ratio were pooled with random effects models, and a summary of receiver operator characteristic (SROC) curves were plotted. The potential heterogeneity was assessed with Q test and I(2) statistics. Subgroup analyses and meta-regressions further investigated the sources of heterogeneity. A total of 77 studies from 48 articles were eligible for the meta-analysis. The results revealed a sensitivity of 0.76, a specificity of 0.81, and an AUC of 0.86 for gastric cancer diagnosis with circulating miRNAs. In addition, subgroup analyses indicated that multiple miRNAs assays, non-microarray screening approaches, and serum-based miRNA assays exhibited good diagnostic performance in contrast to a single miRNA assay, microarray expression profiling screening, and plasma-based miRNA group analysis. The diagnostic ability of miRNAs in early stage I–II groups and the high expression group were approximately similar to that in the stage I–IV groups and the low expression group. For the circulating miRNAs, our meta-analysis identified a combination of multiple miRNAs, non-microarray chip screening, and serum-based miRNA assays were associated with the most effective GC diagnostic performance. However, many unclear molecular mechanisms limited the accuracy of the diagnostic results, and should be interpreted with caution. Further large-scale prospective studies are required for validating the diagnostic applicability of circulating miRNAs in gastric cancer patients.